Metabolic Alterations in FMR1 Premutation Carriers - Cao, Yiqu; Peng, Yun; Kong, Ha Eun; Allen, Emily G.; Jin, Peng (Frontiers in Molecular Biosciences, 2020)
Fragile X-associated tremor/ataxia syndrome (FXTAS) is an adult-onset neurodegenerative disorder caused by an expanded CGG repeat in the 5' UTR of the FMR1 gene. Currently there is no effective treatment for FXTAS, and the development of biomarkers is still in its infancy. Recent metabolic studies have provided promising insight through identification of potential biomarkers and therapeutic pathways. Here we review our latest understanding of the metabolic alterations found in FXTAS patients and disease models, along with our perspective for future studies in this emerging field.